Mucosal immunization of mice with a recombinant Salmonella choleraesuis that expresses a multimeric gonadotropin releasing hormone fusion protein - Kemp, Jeffrey M., author; Graham, James, advisor; Huyvaert, Kathryn P., committee member; Bowen, Richard, committee member; Miller, Lowell, committee member; Rhyan, Jack, committee member (Colorado State University. Libraries, 2011)
To view the abstract, please see the full text of the document.
Keywords: immunocontraception; vaccine stabilization; recombinant bacteria; oral delivery